Underwriting performance: Foreseeing the future of sharia insurance in Indonesia - Widodo, Kharisma Dwi; Lutfiyah, Dinda (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
A healthy underwriting performance is crucial for the sustainability of insurance companies. Effective underwriting enables companies to accurately assess and manage risks, set fair premiums, and avoid unnecessary losses. However, studies on underwriting performance have mostly focused on company-specific factors and/or have only been conducted in developed countries. There is also a lack of specific studies on the role of underwriting performance in sharia insurance (takaful) companies. This study aims to fill that gap by conducting an in-depth analysis of the role of underwriting performance in sharia insurance companies in Indonesia. It also seeks to refine previous research by examining both the short-term and long-term roles of underwriting performance in these companies. The study uses secondary panel data with 20 sharia insurance companies as units of observation. The coefficient estimates in this study are obtained using a dynamic panel data regression approach, to determine the short-term and long-term effects of underwriting performance in sharia insurance. The estimation results of the dynamic panel regression model show that the underwriting variable has a positive and significant effect on sharia insurance premium income, both in the short term (coefficient: 0.1262; sig. 0.021) and in the long term (coefficient: 0.2009; sig. 0.010), with a convergence rate of 2.0697, indicating a relatively fast system adjustment towards equilibrium.